Komunikasi Terapeutik Perubahan Perilaku Kekerasan Pada Pasien Skizofrenia Di Rumah Sakit Jiwa Bina Karsa Medan Tahun 2021 - Devi Naomi; Erita Gustina; Purwaningsih Purwaningsih (Jurnal Kesehatan dan Fisioterapi, 2022)
Mental disorder is a disease caused by confusion of thoughts, perceptions, behavior and not being able to adapt to oneself, others, society, and the environment. Violent behavior is a condition in which a person performs actions that are physically harmful to himself, others and the environment. Therapeutic communication is communication that is consciously planned, aims and its activities are centered on the patient's recovery. The case study method of this research is descriptive. The study sample consisted of 2 patients according to the inclusion criteria, namely schizophrenia patients with violent behavior, cooperative patients and willing to participate in the study from beginning to end, female, aged 29 to 35 years, and patients with violent behavior who were willing to be respondents. The results of the study after being given therapeutic therapy in the first patient experienced changes in violent behavior and the second patient did not experience changes in violent behavior due to differences in background. The purpose of this study is that further researchers are expected to be able to conduct research by adding other characteristics that have not been studied in connection with the symptoms of people with schizophrenia. It is concluded that people with mental disorders or schizophrenia are people who experience mental disorders. It is hoped that the hospital management, especially in the field of mental nursing, should further improve therapeutic communication between nurses and patients.Keywords: Schizophrenia, Violent Behavior, Therapeutic Communication